Localization factors and development strategies for producer services: a case study of Belgrade, Serbia - Gligorijević, Vera; Devedžić, Mirjana; Ratkaj, Ivan (Acta geographica Slovenica, 2014)
This article highlights the patterns of Advanced Producer Services (APS) in Belgrade and relates them to contemporary spatial and economic intrametropolitan transformations. The locational strategies of APS have influenced the creation of another center called New Belgrade next to the traditional central business district (CBD). Over the last ten years, government planning documents and the location preferences of foreign firms have made New Belgrade the most attractive business location in Serbia. In a sample of the leading APS firms in Belgrade, 129 firms are analyzed in terms of firm sector, ownership, and location. The results confirm the multipolar-monocentric pattern, which appears to be a common feature in many European cities.